An archaeological landscape amid nature, culture, and atmosphere: preliminary considerations for the Co.R.A.Ve. Research and Conservation Project - Vagnarelli, Tommaso; Morezzi, Emanuele (Restauro Archeologico, 2024)
The Co.R.A.Ve. research project, initiated by the Polytechnic University of Turin in 2020, focuses on the conservation of archaeological ruins in vegetative contexts, with particular attention to the Etruscan necropolis of Banditaccia in Cerveteri. This site constitutes a unique case of fusion between natural elements and Etruscan artifacts, creating a landscape of extraordinary historical, cultural, and emotional value. The necropolis is distinguished by a symbiosis between native vegetation and funerary structures, posing significant challenges to traditional restoration practices. The article thoroughly examines the complexity of the necropolis landscape, articulated on two scales: the landscape scale, concerning the relationship between monuments and nature, and the detail scale, focusing on individual artifacts. Vegetation, an integral part of the tomb structures, contributes to their aesthetic and historical perception but also presents a conservation challenge. The theories of Carlson and Assunto are employed to frame the landscape as a natural, cultural, and emotional phenomenon, highlighting the importance of human perception and the sentimental dimension. Described as an example of a "historic landscape," the necropolis represents a unique interaction between nature and archaeology. This theoretical approach underscores the need for conservation interventions that maintain the balance between vegetation and ruins, avoiding both neglect and excessive interventions. The analysis of the Cerveteri necropolis landscape provides insights for developing new conservation methodologies that respect the complexity and integrity of the site, contributing to its enhancement and protection for future generations.